Analisis Penyelesaian Soal Geometri Bidang pada Materi Segitiga Berbasis Konteks Budaya Lokal dalam Pembelajaran Matematika - Christania Rossalin Sagala; Aulia Syahputri; Intan Ria Utami Limbong; Yolanda Naomi Sagala; KMA Fauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze students’ solutions to plane geometry problems on triangle topics presented in a local cultural context in mathematics learning. The research employed a qualitative descriptive approach involving 25 second-semester students of the Mathematics Education Study Program at Universitas Negeri Medan. The research instrument consisted of five essay-type geometry problems based on local cultural contexts designed to encourage higher-order thinking skills. Data were analyzed using Newman’s Error Analysis, which includes reading, comprehension, transformation, process skills, and encoding stages. The findings indicate that the highest percentage of errors occurred at the process skill stage (15%), followed by transformation errors (13.3%). Comprehension and encoding errors each accounted for 11.6%, while no reading errors were identified. These results suggest that students still face difficulties in applying mathematical procedures and translating contextual problems into appropriate mathematical models.